Linear in magnetic field increase of the magneto-optical Kerr effect in multilayered Co/Cu films - Lukienko, I.M.; Kharchenko, M.F.; Zorchenko, V.V.; Stetsenko, A.N. (Functional Materials, 2008)
The Kerr rotation, steadily and linearly increasing in magnetic field was observed in the Co/Cu multilayered films at the Cu layer thickness providing the extreme exchange couplings between the Co layers. The enhancement of the Kerr effect in magnetic field is supposed to be caused by increase of the electron density at the Fermi level at the Co/Cu interfaces because of hybridization of the d-(Co) and sp-(Cu) electronic states subjected to the quantum size effect in the Cu layers.